Environmental psychology: A brief review of the field - Chaustre Jota, Daniel (2021)
This paper aims to review the literature about environmental psychology, a field that examines the relation between the individual and the environment. Due to the diversity of approaches to the study of the individual-environment interaction, including social and physical environment as well as natural and artificial environment, a definition of environmental psychology and its main characteristics are presented. Research methods usually applied in the field, as well as levels of analysis (from microenvironment to global environments) are analyzed. Then, two of the most relevant study fields are examined: environmental attitudes and sustainable development. Finally, the future of environmental psychology is discussed, considering the raise of environmental problems and concerns.